1995
DOI: 10.1093/geront/35.3.386
|View full text |Cite
|
Sign up to set email alerts
|

"To Grandmother's House We Go": Health and School Adjustment of Children Raised Solely By Grandparents

Abstract: This manuscript has been reproduced from the microfilm master. UMI films the text directly from the origiral or copy submitted. Thus, some thesis and dissertation copies are in typewriter face, while others may be from any type of computer printer. The quality of this reproduction is dependent upon the quality of the copy submitted. Broken or indistinct print, colored or poor quality illustrations and photographs, print bleedthrough, substandard margins, and improper alignment can adversely aff^ reproduction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(81 citation statements)
references
References 0 publications
5
72
2
Order By: Relevance
“…They did report, however, that an earlier study (Kellam, Ensminger, & Turner; as cited in Solomon & Marx, 1995) suggested that grandparent involvement was positively associated with the psychological well-being and social adjustment of their grandchildren. Jones (1993) proposed that the grandparent-grandchild relationship may provide the nurturing buffer needed to mediate positive adjustment by these children.…”
Section: Children Being Raised Bv Grandparentsmentioning
confidence: 83%
See 4 more Smart Citations
“…They did report, however, that an earlier study (Kellam, Ensminger, & Turner; as cited in Solomon & Marx, 1995) suggested that grandparent involvement was positively associated with the psychological well-being and social adjustment of their grandchildren. Jones (1993) proposed that the grandparent-grandchild relationship may provide the nurturing buffer needed to mediate positive adjustment by these children.…”
Section: Children Being Raised Bv Grandparentsmentioning
confidence: 83%
“…Solomon and Marx (1995) did an epidemiological study, using data from the 1988 National Health Interview Survey, to examine the health and school adjustment of children raised by grandparents. One section of Pruchno's (1999) telephone interviews with 717 custodial grandmothers included items related to the children's behavior and academic performance.…”
Section: Grandparents Assisting In Raising Their Grandchildren Is Notmentioning
confidence: 99%
See 3 more Smart Citations